Molecular Cloning and Expression of Cu/Zn-Containing Superoxide Dismutase from Fasciola hepatica - Kim, Tong-Soo (American Society for Microbiology, 2000)
The cytosolic superoxide dismutase (SOD) of Fasciola hepatica, a causative agent of fascioliasis, was purified and characterized. The enzyme consists of two identical subunits, each with an apparent molecular mass of 17.5 kDa. An analysis of the enzyme's primary structure and inhibition studies revealed that the enzyme is a copper/zinc-containing SOD (Cu/Zn-SOD). The enzyme activity was relatively stable in a broad pH range, from pH 7.0 to 10.0, and the enzyme showed maximum activity at pH 7.5. This enzyme also displayed strong antigenicity against sera of bovine and human subjects with fascioliasis. The SOD gene fragment was amplified by PCR with degenerate oligonucleotide primers derived from amino acid sequences conserved in the Cu/Zn-SODs of other organisms. An F. hepatica cDNA library was screened with the SOD gene fragment as a probe. As a result, a complete gene encoding the Cu/Zn-SOD was identified, and its nucleotide sequence was determined. The gene had an open reading frame of 438 bp and 146 deduced amino acids. Comparison of the deduced amino acid sequence of the enzyme with previously reported Cu/Zn-SOD amino acid sequences revealed considerably high homologies. The coding region of the F. hepatica Cu/Zn-SOD was cloned and expressed in Escherichia coli. Staining of native polyacrylamide gel for SOD activity of the expressed protein revealed SOD activity that was inactivated by potassium cyanide and hydrogen peroxide but not by sodium azide. This means that the presence of the recombinant fusion protein is indicative of Cu/Zn-SOD. The expressed protein also reacted with sera of bovine and human subjects with fascioliasis, but it did not react with sera of uninfected bovine and human subjects.